Conserved and diverged asymmetric gene expression in the brain of teleosts - Agostini, Carolina; Bühler, Anja; Antico Calderone, Alessandra; Aadepu, Narendar; Herder, Cathrin; Loosli, Felix; Carl, Matthias (Frontiers in cell and developmental biology, 2022)
Morphological left-right brain asymmetries are universal phenomena in animals. These features have been studied for decades, but the functional relevance is often unclear. Studies from the zebrafish dorsal diencephalon on the genetics underlying the establishment and function of brain asymmetries have uncovered genes associated with the development of functional brain asymmetries. To gain further insights, comparative studies help to investigate the emergence of asymmetries and underlying genetics in connection to functional adaptation. Evolutionarily distant isogenic medaka inbred lines, that show divergence of complex traits such as morphology, physiology and behavior, are a valuable resource to investigate intra-species variations in a given trait of interest. For a detailed study of asymmetry in the medaka diencephalon we generated molecular probes of ten medaka genes that are expressed asymmetrically in the zebrafish habenulae and pineal complex. We find expression of eight genes in the corresponding brain areas of medaka with differences in the extent of left-right asymmetry compared to zebrafish. Our marker gene analysis of the diverged medaka inbred strains revealed marked inter-strain size differences of the respective expression domains in the parapineal and the habenulae, which we hypothesize may result from strain-specific gene loss. Thus, our analysis reveals both inter-species differences but also intra-species plasticity of gene expression in the teleost dorsal diencephalon. These findings are a starting point showing the potential to identify the genetics underlying the emergence and modulations of asymmetries. They are also the prerequisite to examine whether variance in habenular gene expression may cause variation of behavioral traits.